Risk analytics : data-driven decisions under uncertainty - Rodríguez, Eduardo (Boca Raton, FL : CRC Press, Taylor and Francis, 2023)
"Organizations and institutions are looking for implementing data-driven decision-making processes, business process improvement and methods for advancing faster in innovation. This book is about implementing the analytics process to develop a risk management practice that creates competitive advantages under uncertainty"--
1. Fundamental Concepts 2. Risk Management, Modelling, and Analytics Processes 3. Decision Making under Risk and Its Analytics Support 4. Risk Management and Analytics in Organizations 5. Tools for Risk Management 6. Data Analytics in Risk Management 7. Machine and Statistical Learning in Risk Analytics 8. Dealing with Monitoring the Risk Analytics Process 9. Creation of Actions and Value
Includes bibliographical references and index.
COECS
In English
Keywords: Management -- Statistical methods; Risk assessment -- Data processing; Decision making; Organizational effectiveness